Elimination of spurious solutions from k·p theory with Fourier transform technique and Burt-Foreman operator ordering - Zhao, Qiuji (2013)
To eliminate spurious solutions in the multiple-band k·p theory, we developed the Fourier transform-based k·p approach through combining the Fourier transform technique with Burt-Foreman operator ordering. The performance is perfect for the six-band k·p calculation, and the spurious solutions in the conduction band met in the eight-band calculation can also be easily screened away in the inborn cut-off step in FTM, i.e., choosing a proper order of Fourier truncation. Truncating high-order terms of Fourier coefficients of the envelope function prevents the occurrence of a wild-spreading spectrum of the Fourier expansion coefficients, which can be taken as the signature of spurious solutions.